Modernség, progresszió, Ady Endre és az Ady-Rákosi vita : egy konfliktusos eszmetörténeti pozíció természete és következményei - Pál, József, N. (2008)
This work can be placed on the borderline of literary history and the history of ideas. It aims to position the famous Hungarian poet of the early 20th century, Endre Ady, on the intellectual map of his age, and to point out his place within the relationships of literary modernity and intellectual-social progressivism; it describes the fixation, form and temporal change of the poet's unique position, and shows the human and intellectual consequences of this position, as it relates to a dispute which lasted for half a year, and only seemingly was of a literary nature. The work consists of three major parts. The first is an overview of the mainly intellectual-ideological aspect of the more than eight-decade Ady reception. The overview intends to demonstrate that after 1919, the history of the intellectual reception of Ady's oeuvre split along opposing ideological and political interests which existed already at the time of the debate between Ady and Jenő Rákosi, and were also present in the dispute. That is the reason why it has been impossible to describe that dispute or any disputes around Ady without interests ; and these inheriting oppositions hindered the recognition of Ady's unique position in the history of ideas in Hungary. The middle part describes the development and nature of Ady's position, which, even if within the literary modernity and intellectual-social progressivism, was almost continuously in conflict, beginning from debates around modern literature, the so-called duk-duk affair , almost resulting in a break-up, through the first world war and the Ady-Rákosy dispute. As a part of this description, I am paying attention to the dispositional, socialization-related, role-related, psychological and existential factors. The third part is the description of the dispute in the continuum of Ady's oeuvre. It proposes that in addition to the opposition between Ady and conservative nationalism being impossible to appease, the poet, who deeply internalized the nation's the irresolvable, entrapped situation, remained alone also among literary moderns and within progressive circles. The summary's goal is to describe the conclusions of the dispute, and also the Ady-related aspects of the recurring pitfalls of Hungarian history.